An introduction to probability theory and mathematical statistics - Rohatgi, V. K., 1939-; Saleh, A. K. Md. Ehsanes (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
A well-balanced introduction to probability theory and mathematical statistics Featuring a comprehensive update, An Introduction to Probability and Statistics, Third Edition remains a solid overview to probability theory and mathematical statistics. Divided into three parts, the Third Edition begins by presenting the fundamentals and foundations of probability. The second part addresses statistical inference, and the remaining chapters focus on special topics. Featuring a substantial revision to include recent developments, An Introduction to Probability and Statistics, Third Edition also.
7.2 modes of convergence7.3 weak law of large numbers; 7.4 strong law of large numbers; 7.5 limiting moment generating functions; 7.6 central limit theorem; 7.7 large sample theory; chapter 8parametric point estimation; 8.1 introduction; 8.2 problem of point estimation; 8.3 sufficiency, completeness and ancillarity; 8.4 unbiased estimation; 8.5 unbiased estimation (continued): a lower bound forthe variance of an estimator; 8.6 substitution principle (method of moments); 8.7 maximum likelihood estimators; 8.8 bayes and minimax estimation; 8.9 principle of equivariance
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Probabilities; Mathematical statistics; Mathematical statistics; Probabilities; MATHEMATICS / Applied; MATHEMATICS / Probability & Statistics / General; Mathematical statistics; Mathematics; Probabilities; Electronic books; Electronic books